Analysis of Community Aspirations for the Postponement of the Regional Elections and Rejection of Kades Officials in the Gunungsitoli District - Dimas Melkisedek Setowardana Laia; Eliagus Telaumbanua; Otanius Laia (Dinasti Publisher, 2025)
Villages are the smallest unit in Indonesia with the authority to regulate local government affairs, as regulated in Law Number 6 of 2014. Villages are formed to improve public services and community welfare, based on community initiatives and local conditions. In accordance with the 1945 Constitution and the principle of decentralization, villages play a role in regional autonomy, with the central government giving some of its authority to regions, including villages, to achieve self-reliance and poverty reduction. This study aims to investigate the causes of the postponement of the Village Head Election (Village Head Election) in Gunungsitoli District, as well as the factors that cause the rejection of the Acting Village Head (P.J Village Head) in the region. The type of research that will be used in this approach is a type of naturalistic research or rather qualitative descriptive research. In general, the postponement of the Village Head Election and the appointment of Village Head Officials can face various challenges that have an impact on community participation, social and economic stability, and trust in village government institutions. Community involvement in the decision-making process and communication transparency are key to addressing these issues.